Hubungan Dukungan Keluarga dengan Kepatuhan Minum Obat pada Lansia Penderita Hipertensi di Desa Pokak - Annisa Cahya R; Daryani Daryani (Universitas Muhammadiyah Klaten, 2024)
Increasing age will result in changes in the structure and function of cells, tissues, and organ systems. One ofthe changes in the organ system, namely the cardiovascular system, also undergoes changes such as thickening of the heart valves, decreased ability to pump blood, increased resistance of peripheral blood vessels and atherosclerosis. This causes blood pressure in the blood vessels, so the condition is called hypertension. The purpose of this study is to determine the relationship between family support and medication adherence in elderly people with hypertension in Pokak Village, Ceper District, Klaten Regency. The type of research used quantitative correlation with cross sectional. The population of this study was the elderly with hypertension patients in the elderly posyandu of Pokak Village with a total of 110 elderly people. The results of respondent characteristics in this study, the average age of respondents 68 years. Most respondents consisted of women as many as 58 people (66.7%). Most respondents are married with 62 respondents (71.3%). A total of 47 respondents (54.0%) were not working, the education level of respondents was mostly high school / vocational school as many as 30 people (34.5%). The average blood pressure of respondents was 164/97 mmHg ± 14,540. Family support of respondents was mostly good with 53 people (60.9%). Respondents' compliance in taking medication was mostly low with 36 respondents (41.4%). The results of statistical tests using Spearmen Rho obtained a significance value (p) value of 0.000 (α=0.05), with a coefficient value (r) of 0.674 which means that there is a strong relationship between family support and adherence to taking medication in elderly people with hypertension in Pokak Village, Ceper District, Klaten Regency